M17 NOLCP- direct access to CT scan from primary care: who should be scanned in 72 hours?. (December 2018) - Robinson, RE; Kutubudin, F; Deus, P; Hughes, K; Wight, A
Abstract : Introduction and objectives: Traditional entry to the lung cancer pathway was via NICE urgent referral criteria, with an option for patients to be referred urgently with normal CXR and high suspicion (outside strict NICE guidance for urgent review). The National Optimal Lung Cancer Pathway (NOLCP) changed entry criteria to either abnormal CXR prompting CT or direct access to 72 hour CT scan with normal CXR but high clinical suspicion 'as per NICE guidance'. Current NICE guidance revolves around CXR indications and suggests primary care investigation in cases of normal CXR/absence of haemoptysis. Wirral Lung Unit (WLU) adopted NOLCP in Oct 2017 via paperless system using radiology requests linking primary care with radiology, respiratory and outpatient departments. Referral form for direct access CT included equivalent criteria to traditional faxed referrals however we encountered capacity issues with numbers of requests. We aimed to investigate the PPV for methods of entry to NOLCP and potentially triage primary care referrals appropriately to the accepted standard of 3%. Methods: Review of indications and results of CXR/CT for all patients between January to March 2018 referred into WLU from primary care. Results-: Total- 210 patients. Table 1 shows the outcomes from the two referral routes. Conversion rate to malignancy in the 'flagged CXR' patients was 35% and 15% in those fulfilling NICE urgent criteria referred via primary care CT. 2/56 of the requests were outside strict NICE criteria with low conversion rates to malignancy- one oesophageal and one lung (where no CXR was done pre scan- which would have been abnormal). In this group conversion to all malignancy was 1.8% and lung 0%. Conclusion: NICE promotes urgent referral with a risk threshold PPV above 3% (unexplained haemoptysis/abnormal CXR) but contains no specific guidance for direct CT criteria with normal CXR and absence of haemoptysis. We found these criteria to be similarly applicable to urgent CT requests and suggest 72 hour scans are limited to these cases. We have introduced a separate CT stream for 'concerning symptoms only' (<3 weeks), accepting importance of investigation to aid small numbers of potentially early stage diagnoses in this group.